DISTRIBUTION OF STRESSES IN AN SEMI-INFINITE PLATE WITH CIRCULAR HOLE UNDER ACT CONSTANT DIAMETRICAL FORCE - Пономаренко, Олександр Миколайович; Цідило, Іван Васильович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The problem of stresses concentration in an semi-infinite plate with circular hole under act constant diametrical force is considered. The analysis is developed on the basis of the Airy’s stresses functions in generalized plane stresses and by applying bipolar coordinates.